2010
DOI: 10.1194/jlr.m004325
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide linkage scan identifies multiple quantitative trait loci for HDL-cholesterol levels in families with premature CAD and MI

Abstract: Coronary artery disease (CAD) and its principal clinical complication of acute myocardial infarction (MI) represent the most important causes of death and disability in the developed world. According to the American Heart Association's 2009 statistical update, nearly 16.8 million Americans are affected with CAD, and 7.9 million have had a myocardial infarction. On average, an American will suffer from a coronary event every 26 s, and about every minute somebody will die from one ( 1 ). The lifetime risk of dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…The RCT system comprises the metabolism of HDL and the subsequent transport of cholesterol from the periphery back to the liver, and because of this role, HDL levels have been found to have an inverse relationship with cardiovascular disease . The primary apolipoprotein component of HDL is ApoA‐I, responsible for the free cholesterol loading of HDL from cells by binding to ABCA1 as well as the secretion of apoE, which stimulates lecithin‐cholesterol acyltransferase (LCAT) activity (Fig.…”
Section: Cholesterol and Its Transportmentioning
confidence: 99%
“…The RCT system comprises the metabolism of HDL and the subsequent transport of cholesterol from the periphery back to the liver, and because of this role, HDL levels have been found to have an inverse relationship with cardiovascular disease . The primary apolipoprotein component of HDL is ApoA‐I, responsible for the free cholesterol loading of HDL from cells by binding to ABCA1 as well as the secretion of apoE, which stimulates lecithin‐cholesterol acyltransferase (LCAT) activity (Fig.…”
Section: Cholesterol and Its Transportmentioning
confidence: 99%
“…In a recent scan for atherogenic dyslipidemia, the multinational Genetic Epidemiology of Metabolic Syndrome study (Wyszynski et al, 2005) found significant linkage to plasma HDL‐C levels on chromosome 15q21–23 in Turkish families (Yu et al, 2005). Previous genome‐wide scans showed significant linkage of this region not only to plasma HDL‐C (Almasy et al, 1999; Feitosa et al, 2007; Yang et al, 2010) but also to triglyceride levels (Suto et al, 1999; Austin et al, 2003; Klimes et al, 2003; Rollins et al, 2006; Burgess‐Herbert et al, 2009; Li et al, 2009). Similar linkage was found for plasma HDL‐C and triglyceride levels in the orthologous region in mice and rats (Suto et al, 1999; Klimes et al, 2003; Rollins et al, 2006; Burgess‐Herbert et al, 2009).…”
Section: Introductionmentioning
confidence: 96%
“…Among these three regions, 19q has been linked to lipid quantitative traits with the most consistent linkage evidence in the previous reports, with LOD scores ranging from 1.9 to 5.7 in the region at 50-70 cM among various populations ( 5,13,16,(53)(54)(55)(56)(57) ( Table 3 ). Similarly, 15q has previously been implicated in several genome scans of lipid-related traits, with LOD scores from 1.8 to 4.2 in the region at 61-72 cM among various populations ( 17,(58)(59)(60)(61)(62) ( Table 3 ). For 20p12, two studies have shown evidence for linkage in this region: a LOD score of 2.8 for TG at 28 cM in an African sibling sample of the Hypertension Genetic Epidemiology Network (HyperGEN) ( 63 ), and 1.6 for LDL-C in French Canadian families ( 55 ).…”
Section: Discussionmentioning
confidence: 99%